The Landscape of Secondary Genetic Rearrangements in Pediatric Patients with B-Cell Acute Lymphoblastic Leukemia with t(12;21) - Agnieszka Kaczmarska; Justyna Derebas; Michalina Pinkosz; Maciej Niedźwiecki; Monika Lejman (Cells, 2023)
The most frequent chromosomal rearrangement in childhood B-cell acute lymphoblastic leukemia (B-ALL) is translocation t(12;21)(p13;q22). It results in the fusion of the ETV6::RUNX1 gene, which is active in the regulation of multiple crucial cellular pathways. Recent studies hypothesize that many translocations are influenced by RAG-initiated deletions, as well as defects in the RAS and NRAS pathways. According to a “two-hit” model for the molecular pathogenesis of pediatric ETV6::RUNX1-positive B-ALL, the t(12;21) translocation requires leukemia-causing secondary mutations. Patients with ETV6::RUNX1 express up to 60 different aberrations, which highlights the heterogeneity of this B-ALL subtype and is reflected in differences in patient response to treatment and chances of relapse. Most studies of secondary genetic changes have concentrated on deletions of the normal, non-rearranged ETV6 allele. Other predominant structural changes included deletions of chromosomes 6q and 9p, loss of entire chromosomes X, 8, and 13, duplications of chromosome 4q, or trisomy of chromosomes 21 and 16, but the impact of these changes on overall survival remains unclarified. An equally genetically diverse group is the recently identified new B-ALL subtype ETV6::RUNX1-like ALL. In our review, we provide a comprehensive description of recurrent secondary mutations in pediatric B-ALL with t(12;21) to emphasize the value of investigating detailed molecular mechanisms in ETV6::RUNX1-positive B-ALL, both for our understanding of the etiology of the disease and for future clinical advances in patient treatment and management.